Filosofia selvatica. Una rivisitazione del pensiero wilderness - SCARPELLI, GIACOMO (S&F_scienzaefilosofia.it, 2020)
Wild Philosophy. Revisiting wilderness Thought The notion of nature has been changing during the last two centuries: from an antagonist that must be conquered, to the environment of which the Homo sapiens is part of. Perhaps this second notion of nature is subjective too. Thoreau considered nature a free creative force and a resource that can decrease but never grows. It is precious for manhood only if humanity understands it is independent and self-governing. Consequently, the man should preserve habitat and prevent its transformation in exclusively human world. But recreating a wild environment, isn’t it an artifice? Will nature be transformed in a mummified representation or pathetic caricature of itself? Does the preservation of wild nature really improve the quality of life? Probably yes, if preservation is not recreation, and if quality of life is quality of life of all species. Certainly, something good is coming for manhood because we will stop to think only of ourselves.